The Effect of Career Scoring and Talent Management on Work Unit Performance with AKHLAK Culture as a Moderating Variable - Adi Chahya Nugraha; Eka Yudhyani; Sayid Irwan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Work unit performance is a critical indicator of organizational effectiveness, reflecting productivity, efficiency, and quality outcomes. Fluctuating performance trends highlight the need to examine how career scoring systems, talent management, and organizational culture interact to influence unit-level results. This study investigated how the career scoring system and talent management influence work unit performance and whether the AKHLAK culture moderates these relationships. A quantitative design was applied, and data from 64 employees were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that the career scoring system has a positive and significant effect on work unit performance, and talent management also exerts a positive and significant effect. Moderation testing confirms that AKHLAK significantly conditions both relationships, with a negative interaction on the career scoring system and a positive interaction on the talent management. The discussion emphasizes that formal human resource practices do not operate uniformly. Effectiveness depends on the extent to which AKHLAK values are internalized in everyday work behaviors, positioning organizational culture as a critical boundary condition for improving unit-level outcomes.